SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN KOS AREA INSTITUT TEKNOLOGI KALIMANTAN BALIKPAPAN DENGAN METODE SIMPLE MULTI ATTRIBUTE RATING TECHNIQUE (SMART) - Dilfa Amalia GF; Nisa Rizqiya Fadhliana; Tegar Palyus Fiqar (Program Studi Sistem Informasi, Universitas Banten Jaya, 2023)
Boarding houses or commonly known as boarding house, is a temporary residence for students who are still in college. The quantity of boarding houses with several criteria offered in the area of Kalimantan Institute of Technology km.15 Balikpapan, makes them to be considered by the students to determine their choices. These excessive alternatives cause the students to visit those boarding houses beforehand to know the criteria each boarding house has and offers. The more boarding house information obtained, the more confused the students feel in deciding which boarding house fits the needs and wants. Therefore, to overcome this problem, a study is conducted, entitled “Decision Support System for Boarding House Selection in the Area of Kalimantan Institute of Technology Balikpapan Accompanied by Simple Multi Attribute Rating Technique (SMART) Method”. Based on the survey in testing the decision support system for selecting the boarding house, several results were obtained, such as blackbox testing for the system and the results of the user perspective percentage of 96%.